The Aztec economic world merchants and markets in ancient Mesoamerica - Hirth, Kenneth 1949- (Cambridge University Press, 2016)
This study explores the organization, scale, complexity, and integration of Aztec commerce across Mesoamerica at Spanish contact. The aims of the book are threefold. The first is to construct an in-depth understanding of the economic organization of precolumbian Aztec society and how it developed in the way that it did. The second is to explore the livelihoods of the individuals who bought, sold, and moved goods across a cultural landscape that lacked both navigable rivers and animal transport. Finally, this study models Aztec economy in a way that facilitates its comparison to other ancient and premodern societies around the world.  What makes the Aztec economy unique is that it developed one of the most sophisticated market economies in the ancient world in a society with one of the worse transportation systems. This is the first book to provide an updated and comprehensive view of the Aztec economy in thirty years
Title from publisher's bibliographic system (viewed on 05 May 2016)
Keywords: Geschichte; Wirtschaft; Aztecs / Economic conditions; Aztecs / Commerce; Merchants / Mexico / History / To 1500; Indians of Mexico / Economic conditions; Indians of Mexico / Commerce / History / To 1500; Azteken; Präkolumbische Zeit; Mexiko